No Weight Catch-Up Growth of SGA Infants Is Associated with Impaired Insulin Sensitivity during the Early Postnatal Period - Tong-yan Han; Xin-li Wang; Yun-pu Cui; Hong-mao Ye; Xiao-mei Tong; Mei-hua Piao (Hindawi Limited, 2010)
Objective. To investigate the relationship between weight catch-up growth and insulin sensitivity in small for gestational age (SGA) infants. Methods. Forty-four singleton SGA subjects met the inclusion criteria and finished-3-month followup. Body weight, length, fasting glucose, and fasting insulin (FI) levels were measured at 3 days and 3 months. Insulin sensitivity was evaluated by FI and homeostasis model assessment (HOMA). Results. According to the change of weight Z-score, forty-four subjects were divided into two groups: noncatch-up growth (NCUG) and catch-up growth (CUG). By 3 months of age, the body weight, body length and BMI of NCUG group were significantly lower than those of CUG group. The FI and HOMA were significantly higher in NCUG group. The change of weight Z-score during 3 months was inversely related to the HOMA at 3 months. Conclusion. Our data exemplified that no weight catch-up growth during the first 3 months was associated with impaired insulin sensitivity in SGA infants.